Grundtvig-manuskripter og grundtvigiana i Det kgl. Bibliotek erhvervet 1963 - maj 1972 - Johansen, Steen (Grundtvig-studier, 1972)
Grundtvig manuscripts and Grundtvigiana in Det kgl. Bibliotek acquired 1963 - May 1912 Compiled by Steen Johansen This commented register may be regarded as a supplement to Registrant over N. F. S. Grundtvigs efterladte Papirer, or “ Grundtvig-Registranten” , which was published 1957-64. It shows that discoveries are still being made of new Grundtvig manuscripts, which are included in the collections of Det kgl. Bibliotek, among these two private collections which the liberary has acquired from Mr. Mogens Müllertz in 1968 (NkS 4680, 40) and from Mr. T . Troensegård in 1970, respectively. Three previously unknown letters from Grundtvig, dated 1812, 1826, and 1857, are rendered as specimens.